Predictors for cannabis cessation during pregnancy: a 10-year cohort study - Maia Brik; Miguel Sandonis; Carmen Cabeza Oliver; Joaquín Temprado; Alina Hernández Fleury; Elena Sánchez Echevarria; Elena Carreras (Journal of Psychosomatic Obstetrics and Gynecology)
The aim of this study is to determine factors associated with cannabis discontinuation, to assess the impact of mental health and addiction interventions on cannabis discontinuation during pregnancy and to investigate the neonatal impact of cannabis discontinuation. This is a 10-year cohort study in a tertiary hospital in Barcelona, Spain, including women with self-reported cannabis use during pregnancy. Main outcome was cannabis discontinuation based on biological sample testing. Secondary outcomes were neonatal intensive care unit (NICU) admission, preterm birth, birth weight and bottle-feeding. When cannabis use was detected during pregnancy, 32 out of 81 (38.3%) discontinued cannabis during pregnancy vs. four out of 61 (6.6%) when detected at birth (p < .001). Multivariate binary logistic regression showed that null parity (OR: 6.95, p = .011), detection of cannabis use during pregnancy (OR: 5.35, p = .018) and early detection and referral to mental health care for counseling on cannabis cessation and interventions on the first trimester (OR: 25.46, p < .001) increased cannabis discontinuation. Risk for preterm birth <37 weeks (11.4% vs. 30.8%) and NICU admission (25.7% vs. 54.2%) were lower when discontinuation. Early detection of cannabis use during pregnancy, cessation counseling with mental health interventions, and null parity are predictors for cannabis discontinuation during pregnancy.